The Role of Social Assistants with Community Independence - Yana Sundayani; Zainal Fadri (Alfuad: Jurnal Sosial Keagamaan, 2024)
The role of social assistants has a correlation with community independence. The social assistance program aims to empower the community to be socially and economically independent so that they are not fully dependent on government assistance. The role of the companion becomes very important in the effort of community independence. The method used is a survey of social assistants with sample selection techniques using random samples and using a Likert scale. The Pearson Product Moment test result of 0.835 means that the role of social assistants with community independence is highly correlated.